Advances in Facial Composite Technology, Utilizing Holistic Construction, Do Not Lead to an Increase in Eyewitness Misidentifications Compared to Older Feature-Based Systems - Pike, Graham E.; Brace, Nicola A.; Turner, Jim; Ness, Hayley; Vredeveldt, Annelies (Frontiers in Psychology, 2019)
An eyewitness can contribute to a police investigation both by creating a composite image of the face of the perpetrator and by attempting to identify them during an identification procedure. This raises the potential issue that creating a composite of a perpetrator might then interfere with the subsequent identification of that perpetrator. Previous research exploring this issue has tended to use older feature-based composite systems, but the introduction of new holistic composite systems is an important development as they were designed to be a better match for human cognition and are likely to interact with memory in a different way. This issue was explored in the current experiment. Participants were randomly assigned to either a feature-based composite construction condition (using E-FIT), a holistic-based composite construction condition (using EFIT-V) or a control condition. An ecologically valid delay between seeing a staged crime, creating the composite and completing the identification task was employed to better match conditions in real investigations. The results showed that neither type of composite construction had an effect on participants’ accuracy on a subsequent identification task. This suggests that facial composite systems, including holistic systems, may not negatively impact subsequent eyewitness identification evidence.